The impact of real life treatment strategies for Candida peritonitis: a retrospective analysis - Dubler, Simon; Laun, M.; Koch, C.; Hecker, Andreas; Weiterer, Sebastian; Siegler, Benedikt Hermann; Röhrig, Rainer; Weigand, Markus A.; Lichtenstern, Christoph (Mycoses, 2017)
Candida species are commonly detected isolates from abdominal foci. The question remains as to who would benefit from early empiric treatment in cases of Candida peritonitis. This study collected real-life data on critically ill patients with Candida peritonitis to estimate the relevance of the chosen treatment strategy on the outcome of these patients. One hundred and thirty-seven surgical intensive care unit (ICU) patients with intra-abdominal invasive Candidiasis were included in the study. Fifty-six patients did not get any antifungal agent. Twenty-nine patients were empirically treated, and 52 patients were specifically treated. In the group without, with empiric and with specific antifungal treatment, the 30-day mortality rate was 33.9, 48.3 and 44.2 respectively. Candida albicans was the most frequently found species. Seven patients in the specific treatment group and one patient in the empiric treatment group emerged with candidaemia. Age, leucocyte count, APACHE II Score and acute liver failure were independent predictors of 30-day mortality in patients with Candida peritonitis. Not all patients with Candida peritonitis received antifungal treatment in real clinical practice. Patients with higher morbidity more often got antifungals. Early empirical therapy has not been associated with a better 30-day mortality.
First published: 03 April 2017
Gesehen am 19.09.2018